2017
DOI: 10.1038/s41598-017-15466-7
|View full text |Cite
|
Sign up to set email alerts
|

ABMA, a small molecule that inhibits intracellular toxins and pathogens by interfering with late endosomal compartments

Abstract: Intracellular pathogenic microorganisms and toxins exploit host cell mechanisms to enter, exert their deleterious effects as well as hijack host nutrition for their development. A potential approach to treat multiple pathogen infections and that should not induce drug resistance is the use of small molecules that target host components. We identified the compound 1-adamantyl (5-bromo-2-methoxybenzyl) amine (ABMA) from a cell-based high throughput screening for its capacity to protect human cells and mice again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 48 publications
(64 reference statements)
3
39
0
Order By: Relevance
“…Outbreaks of emerging pathogens without licensed treatments and with microbial drug-resistance are major public health threats [1][2][3]. An emerging strategy in anti-infectious drug discovery is to look for therapies targeting host functions, which are exploited by pathogens for infection and/or growth in host cells [4][5][6][7][8][9][10][11][12][13]. The endo-lysosomal system is made of dynamic organelles (early endosomes, recycling endosomes, late endosomes and lysosomes) into which cargo molecules are internalized, transported, recycled or digested for cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of emerging pathogens without licensed treatments and with microbial drug-resistance are major public health threats [1][2][3]. An emerging strategy in anti-infectious drug discovery is to look for therapies targeting host functions, which are exploited by pathogens for infection and/or growth in host cells [4][5][6][7][8][9][10][11][12][13]. The endo-lysosomal system is made of dynamic organelles (early endosomes, recycling endosomes, late endosomes and lysosomes) into which cargo molecules are internalized, transported, recycled or digested for cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is current practice in drug discovery processes to pretreat cells with the compound before infection, in order to better monitor a positive effect. ABMA was tested for anti-HSV-2 activity with treatment administered from 5 h before infection to the end of the assays, as reported previously [ 15 ]. As shown in Figure 2 B and Table 1 , ABMA inhibited HSV-2-induced CPE in a dose-dependent manner with an EC 50 value of 1.66 μM and a maximum inhibition rate of 93.36% at 3.13 μM.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of an available vaccine and the emergence of drug resistance highlight the importance of developing alternative antivirals against HSV-2 with distinct modes of action [ 10 ]. ABMA has been demonstrated previously to be active against several intracellular pathogens exploiting host–vesicle transport [ 15 ]. Here we demonstrated that ABMA is an effective inhibitor of HSV-2, in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations